Analysis of Red Onion Hydroponic Cultivation Case Study at Fresh Hydroponic MSMEs - Andri Krisna Dianto; Dwiyana Anela kurniasari; Heri Susanto; Faisol Humaidi (Faculty of Agriculture, Merdeka University Surabaya, Indonesia, 2023)
The purpose of the study is to find out the process of cultivating shallots using hydroponic techniques. The location of the study was conducted in Kedamean District, Gresik Regency, precisely Turirejo Village, which has fresh hydroponic Micro, Small and Medium Enterprises (MSMEs). The determination of the location of the study was carried out purposively, namely carried out on fresh hydroponic MSMEs with a business of cultivating shallot commodities hydroponically without using green houses or shade. The data used by researchers are primary and secondary data. The research method uses a descriptive method that uses survey methods, in-depth interviews and observations as data collection techniques. The results of the analysis of the hydroponic cultivation process of fresh hydroponic MSMEs are cultivating hydroponic shallots with the Nutrient Film Technique (NFT) system. It consists of 2 stages including, seedbed installation and enlargement installation. The cultivation process is carried out in an open place, namely the yard of the house or not using a greenhouse. The hydroponic cultivation process in fresh hydroponic MSMEs starts from the preparation of cultivation, the process of cultivating shallot hydroponics and post-harvest handling. Preparation for hydroponic cultivation of shallots includes capital, land, labor and saprodi. The next stage is in the cultivation process, including 1) Seeding seedlings, 2) Transplanting, 3) maintenance: (fertilization embroidery, watering, opt control) 4) Harvesting. Post-harvest handling in the hydroponic cultivation of shallots, namely withering and drying.